2021
DOI: 10.21203/rs.3.rs-990197/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-molecule-mediated OGG1 inhibition attenuates pulmonary inflammation and lung fibrosis

Abstract: Interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF) are caused by persistent micro-injuries to alveolar epithelial tissues accompanied by aberrant repair processes. Despite substantial advancement in our understanding of IPF progression, numerous questions remain concerning disease pathology. IPF is currently treated with pirfenidone and nintedanib, compounds which slow the rate of disease progression but fail to target underlying pathophysiological mechanisms. The DNA repair enzyme 8-oxogua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Treatment with TH5487 also decreased collagen deposition and structural deformation of the alveoli, indicating that TH5487 may be an effective inhibitor of bleomycin-induced fibrosis as characterized by histological lung damage. Finally, TH5487 decreased immune cell recruitment, levels of proinflammatory and profibrotic mediators in addition to alleviating weight loss and rejuvenating pulmonary health in experimental animals (94). These data show promising preclinical support for future studies investigating the clinical utility of TH5487 for treatment of IPF.…”
Section: Potential Clinical Utility Of Ogg1 Inhibitors In Treatment O...mentioning
confidence: 69%
See 4 more Smart Citations
“…Treatment with TH5487 also decreased collagen deposition and structural deformation of the alveoli, indicating that TH5487 may be an effective inhibitor of bleomycin-induced fibrosis as characterized by histological lung damage. Finally, TH5487 decreased immune cell recruitment, levels of proinflammatory and profibrotic mediators in addition to alleviating weight loss and rejuvenating pulmonary health in experimental animals (94). These data show promising preclinical support for future studies investigating the clinical utility of TH5487 for treatment of IPF.…”
Section: Potential Clinical Utility Of Ogg1 Inhibitors In Treatment O...mentioning
confidence: 69%
“…OGG1targeting siRNA and inhibition (TH5487) of OGG1 significantly inhibit pro-migratory effects of TGFb. Bioanalytical liquid chromatography tandem mass spectrometry data-independent acquisition (LC-MS/MS DIA) analysis showed significant downregulation of OGG1-dependent GO terms, including collagen biosynthesis processes, wound healing involved in inflammatory response, endothelial cell proliferation, collagen metabolic processes, response to fibroblast growth factor, regulation of cytokine production, wound healing, and response to wounding in fibrotic tissue (94). These studies suggest that TH5487 is clinically relevant to the observed decreases in fibrotic processes.…”
Section: Potential Clinical Utility Of Ogg1 Inhibitors In Treatment O...mentioning
confidence: 77%
See 3 more Smart Citations